THE MAIN TASK IS THE IMPROVEMENT OF THE ORGANIZATIONAL AND ECONOMIC MECHANISM FOR THE DEVELOPMENT OF RUSSIAN ENTERPRISES - G. B. Kleiner; N. L. Pirogov (Модернизация, инновация, развитие, 2018)
Purpose: the purpose of this article is to justify the choice of the strategic direction of effective development of the national economy of Russia. The authors see the solution of this problem on the way of improving the organizational and economic mechanism of the functioning of Russian enterprises. This problem is considered to be one of the main authors in the consolidation of society and its mobilization for the implementation of the tasks set in the may Decree of the President of the Russian Federation (№ 204 from 2018).Methods: the study was conducted using the methods of systematic, logical, comparative analysis, involving Russian and foreign experience in solving social and economic problems. Particular attention was paid to the validity of the conclusions.Results: national economic problems are touched upon through the prism of the economy of enterprises. An attempt has been made to prove the dependence of the acceleration of the rates of economic development on the improvement of the enterprise's internal economic mechanism. In the postindustrial society, the role of enterprises as the main link in the production of material goods and the provision of services is not diminished, despite the accelerated introduction of scientific and technological progress and the increase in the value of personal property. The improvement of the internal structure of enterprises proposed in the article can significantly reduce the negative consequences of the privatization of state property. According to the authors, this will improve the efficiency of the use of human capital in terms of all its components: ordinary workers, managers, specialists, owners.Conclusions and Relevance: currently, there is a situation in which the owners of enterprises (mainly large ones) have practically unlimited rights and very limited liability for the results of the work of their enterprises. This situation hinders the development of the productive forces of society. The proposed concept of an "effective enterprise" means solidary management of enterprises (ultimately solidary management of the economy). It provides for a system of measures to remedy the situation. The first steps in this direction are the following: 1) the creation of a balanced system of enterprise management; 2) democratization of management and development of the institution of collective (people's) enterprises; 3) the movement in the direction of restraint unrestrained competition and finding ways of cooperation not only within enterprises but also in the relations between all participants of the process of production and realization of products, as well as authorities at all levels; 4) streamlining the processes for the establishment and liquidation of enterprises; 5) the active implementation of multilevel and multidimensional strategic planning. It is not possible to implement these measures in a short time. But the movement along this path creates systemic conditions for accelerating economic growth.